Legal Protection of Auction Buyers of Mortgage Objects Canceled by Court at the State Property Service Office and Auctions - Yusuf, Adrian Hasfi; Gunarto, Gunarto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to: analyze the legal remedies of mortgaged object buyers at the State Property Service Office and Auctions that were canceled, To analyze the legal protection of mortgaged object auction buyers at the State Property and Auction Services Office which were canceled by the court, To analyze the mortgage objects in Office of the State Assets and Auction Service which was canceled by the court. Research Methods: The empirical juridical approach is that this research means that in analyzing the problem, it is done by combining legal materials (which are secondary data) with primary data obtained in the field, namely about